LncRNA MEG3 Protects Chondrocytes From IL-1β-Induced Inflammation via Regulating miR-9-5p/KLF4 Axis - Huang, Yijiang; Chen, Daosen; Yan, Zijian; Zhan, Jingdi; Xue, Xinghe; Pan, Xiaoyun; Yu, Huachen (Frontiers in Physiology, 2021)
Background Osteoarthritis (OA) is a chronic degenerative disease of the joints characterized by articular cartilage damage, subchondral bone remodeling, osteophyte formation, and inflammatory changes. This work aims to investigate the protective role of long non-coding RNA (lncRNA) maternally expressed 3 (MEG3) against the apoptosis of chondrocytes. Methods Chondrocyte cell lines, CHON-001, and ATDC5 were treated with different doses of interleukin-1β (IL-1β) to mimic the inflammatory response during OA pathogenesis. Quantitative real-time polymerase chain reaction was performed to measure MEG3, miR-9-5p, and Krüppel-like factor 4 (KLF4) mRNA expression levels. MEG3 and KLF4 overexpression plasmids, MEG3 shRNA, miR-9-5p mimics, and miR-9-5p inhibitors were transfected into the cells. Cell counting kit-8, wound healing assay, and flow cytometry were conducted to determine cell viability, migration, and apoptotic rate. Dual-luciferase reporter assay was adopted to verify the targeting relationships among MEG3, miR-9-5p, and KLF4. Western blot was used to detect KLF4 protein expression. Enzyme-linked immunosorbent assay was employed to measure the levels of inflammatory factors. Results MEG3 expression in chondrocytes was down-regulated by the stimulation of IL-1β, and MEG3 negatively regulated miR-9-5p expression but positively regulated KLF4 expression. MEG3 overexpression strengthened the viability and migration of CHON-001 and ATDC5 cells but restrained the apoptosis and inflammatory response, while MEG3 knockdown had opposite effects. miR-9-5p inhibition or KLF4 overexpression could counteract the effects of MEG3 knockdown on chondrocytes. Besides that, MEG3 was proved to be a molecular sponge for miR-9-5p, and KLF4 was verified as the target of miR-9-5p. Conclusion MEG3 can promote chondrocyte proliferation and migration and inhibit apoptosis and inflammation by sponging miR-9-5p to induce KLF4 expression, which provides a promising therapy target for OA treatment.